CCP encyclopedia of Philippine art the multimedia CD-ROM edition. (Cultural Center of the Philippines and Distributed Processing Systems, Inc, 1998)
Previously published in 10 volumes in 1994, this CD-ROM edition of Philippine art provides an enriching multimedia tour of the Philippine cultural landscape, as live and practiced by the Peoples of the Philippines and expressed in music, dance, literature, architecture, visual arts, film, and theater -- container.